Quantification of selected bioactive compounds in instant coffee and their effect on gastric release using HGT-1 Cells - Wan Kamarul Zaman, Wan Syamimi; Loh, Su Peng; Mohd Esa, Norhaizan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: This study was carried out to quantify the selected bioactive compounds (i.e., chlorogenic acids, caffeine, and N-methylpyridinium) in instant coffee and to analyze its correlation with the gastric release effect of the HGT-1 cell line. Methods: Selected bioactive compounds in regular (REG), low sugar (LS), low fat (LF), white coffee (WC), white coffee low acid (WCA), decaffeinated (DC), and instant black coffee (BC) were quantified using HPLCDAD (high-performance liquid chromatography diode array detection) system and flow cytometry analysis for its gastric release effect when treated with HGT-1 cell. Results: The HPLC data showed the content of caffeine (60,212 ± 212 µg/ml) and chlorogenic acid (35,779 ± 3027 µg/ml) were significantly high in BC while the lowest caffeine value was found in DC coffee. Chlorogenic acid in other instant coffee samples showed insignificant content distinctions. As for N-methylpyridinium (NMP), the highest content was found in BC (565 µg/ml) and the lowest value was detected in WC (52 µg/ml) coffee. Gastric release activity by HGT-1 cells was significantly higher in DC and REG coffee treatment. Pearson correlation showed no significant correlation between the quantitative data and gastric release activity by HGT-1 cells. Conclusion: The selected bioactive compounds contained in instant coffees were unable to stimulate gastric release.